The structural impacts of enforcement policy on Latino immigrant health - Maria-Elena De Trinidad Young; Denise Diaz Payan; Iris Y. Guzman-Ruiz (Frontiers Media S.A., 2022)
As evidence of the negative health impact of immigration enforcement policy continues to mount, public health research has focused primarily on the psychosocial health mechanisms, such as fear and stress, by which immigration enforcement may harm health. We build on this research using structural vulnerability theory to investigate the structural processes by which enforcement policy may shape Latino immigrants' health. We conducted qualitative analysis of testimonios from a purposive sample of Latino immigrants (n=14) living in Southern California in 2015, a period of significant federal, state, and local enforcement policy change. Testimonios are a narrative methodology used across the social sciences and humanities to center the voices of marginalized people. Through unstructured testimonio interviews, we sought to understand Latino immigrants' experiences with immigration enforcement and identify specific structural factors by which those experiences may influence health. Respondents' narratives revealed that singular enforcement experiences were not viewed as the sole manifestation of enforcement, but as part of a system of intersecting physical, legal, institutional, and economic exclusions which shaped the social and economic conditions that influence health. These exclusions reinforced respondents' marginalization, produced instability about the future, and generated a sense of individual responsibility and blame. We discuss how physical, legal, institutional, and economic processes may influence health and propose a framework to inform population health research on intersecting structural health mechanisms.